Мотивація персоналу як чинник підвищення ефективності використання трудових ресурсів - Побережна, Наталія Миколаївна; Жарков, Вадим Миколайович (НТУ "ХПІ", 2014)
У статті досліджено теоретичні підходи до мотивації персоналу на основі робіт науковців. Розглянуто мотивацію як процес виникнення та задоволення потреб працівників із використанням шести стадій. Проаналізовано досвід провідних країн світу щодо питань стимулювання. Надані практичні рекомендації застосування окремих мотиваційних заходів для сучасних вітчизняних підприємств.

In the article theoretical approaches to motivating employees on basis of scientists’ work are examined in this research paper. Motivation is considered as the process of appearance and satisfaction of needs and wants of employees in six stages. Experience of the world’s leading countries concerning stimulation is analyzed. Clearly designed to stimulate the process of allowing labor collectives long-term function effectively without interference management entity. Practical recommendations on application of specific motivational measures for modern domestic enterprises are given. Creation of Ukrainian enterprises effective motivation systems is impossible without studying the experience of advanced countries. Thus, the modern Ukrainian companies should review the system of bonuses of employees depending on the specific company, its business property.
Motivation as a factor in increasing the efficiency of utilization of labor resources
Keywords: мотивація персоналу; стимулювання; колектив; винагорода; мотиваційні заходи; motivation; stimulation; collective; reward